Implementation of healthy food environment policies to prevent nutrition-related non-communicable diseases in Ghana: National experts' assessment of government action. (May 2020) - Laar, Amos; Barnes, Amy; Aryeetey, Richmond; Tandoh, Akua; Bash, Kristin; Mensah, Kobby; Zotor, Francis; Vandevijvere, Stefanie; Holdsworth, Michelle
Highlights: There is insufficient implementation of food environment policies in Ghana. Government action to restrict marketing of breastmilk substitutes is advanced in Ghana. Legislation to regulate advertising/sale of unhealthy food is an identified priority. Leadership, monitoring and evaluation are needed to support policy infrastructure. Funding for nationally relevant research on NCDs is a high infrastructure priority. Abstract: Nutrition-related non-communicable diseases (NR-NCDs) are a global health problem, increasingly recognised as driven by unhealthy food environments. Yet little is known about government action to implement food environment-relevant policies, particularly in low-and lower-middle income countries. This study assessed government action, implementation gaps, and priorities to improve the food environment in Ghana. Using the Healthy Food-Environment Policy Index (Food-EPI), a panel comprising government and independent experts (n = 19) rated government action to improve the healthiness of food environment in Ghana against international best practices and according to steps within a policy cycle. Forty-three good practice indicators of food environment policy and infrastructure support were used, with ratings informed by systematically collected evidence of action validated by government officials. Following the rating exercise, the expert panel proposed and prioritized actions for government implementation. Three-quarters of all good practice indicators were rated at 'low'/'very little' implementation. Restricting the marketing of breast milk substitutes was the only indicator rated "very high". Of ten policy actions prioritized for implementation, restricting unhealthy food marketing in children's settings and in the media were ranked the highest priority. Providing sufficient funds for nationally-relevant research on nutrition and NCDs was the highest priority infrastructure-support action. Other priority infrastructure-support actions related to leadership, monitoring and evaluation. This study identified gaps in Ghana's implementation of internationally-recommended policies to promote healthy food environments. National stakeholders recommended actions, which will require legislation and leadership. The findings provide a baseline for measuring government progress towards implementing effective policies to prevent NR-NCDs.